Generasi Z: Apa Gaya Belajar yang Ideal di Era Serba Digital? - Manjillatul Urba; Annisa Ramadhani; Arikah Putri Afriani; Ade Suryanda (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
The Generation Z is often referred to as the internet generation, born between the year 1997-2012, where they came into existence during a time of advanced and modern technology. The development of digital technology, such as sophisticated smartphones, has made it easy and fast for society to obtain various information through the internet. In the field of education, digital-based learning has been implemented by integrating learning content in the form of audio and visual images presented by teachers, accessible to students through websites. With the change in the learning approach, it undoubtedly influences the learning style of a student. Essentially, the learning style of each individual differs from others. Therefore, this research aims to identify the ideal learning style, especially for Generation Z, which coexists with digital media-based learning. Based on existing data and referring to a specific article source, the ideal learning style in this digital era is considered to be audiovisual learning. This involves a combination of sound and visual imagery, such as video simulations, which facilitate students in understanding the content of learning materials.